PENGARUH MOTIVASI, LINGKUNGAN KERJA, KOMPETENSI, DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI DI LINGKUNGAN KANTOR DINAS PEKERJAAN UMUM PROVINSI BALI - Anak Agung Ngurah Bagus Dhermawan; I Gde Adnyana Sudibya; I Wayan Mudiartha Utama (Faculty of Economics and Business Udayana University, 2012)
The purpose of this research are to know the influence of motivation, work environment, competence and compensation toward work satisfaction and employees performance in Public Work Agency of Bali Province. 150 sample were selected by stratified proportional random sampling among Public Work Agency of Bali Province employees. Data were collected by questionnaires and SEM were applies as an analysis technique. Based on statistical analysis, motivation and work environment have not significant influence toward work satisfaction but competence and compensation does have. Motivation and competence do not have significant influence toward employees performance but work environment and compensation does have. The implication is motivation, work environment, competence, and compensation need to be increased in order to improve employees work satisfaction. The increase of work satisfaction will be able to improveemployees performance